'Striking the Right Balance' in Targeting PPARγ in the Metabolic Syndrome: Novel Insights from Human Genetic Studies. (19th March 2007) - Gurnell, Mark
Abstract : At a time when the twin epidemics of obesity and type 2 diabetes threaten to engulf even the most well-resourced Western healthcare systems, the nuclear receptor peroxisome proliferator-activated receptorγ (PPARγ ) has emerged as a bona fide therapeutic target for treating human metabolic disease. The novel insulin-sensitizing antidiabetic thiazolidinediones (TZDs, e.g., rosiglitazone, pioglitazone), which are licensed for use in the treatment of type 2 diabetes, are high-affinity PPARγ ligands, whose beneficial effects extend beyond improvement in glycaemic control to include amelioration of dyslipidaemia, lowering of blood pressure, and favourable modulation of macrophage lipid handling and inflammatory responses. However, a major drawback to the clinical use of exisiting TZDs is weight gain, reflecting both enhanced adipogenesis and fluid retention, neither of which is desirable in a population that is already overweight and prone to cardiovascular disease. Accordingly, the ''search is on'' to identify the next generation of PPARγ modulators that will promote maximal clinical benefit by targeting specific facets of the metabolic syndrome (glucose intolerance/diabetes, dyslipidaemia, and hypertension), while simultaneously avoiding undesirable side effects of PPARγ activation (e.g., weight gain). This paper outlines the important clinical and laboratory observations made in human subjects harboring genetic variations in PPARγ that support such a therapeutic strategy.